Consumption as a moral action: A Critical reading on philosophical approaches to consumption - Seid Ali Asghar Hashem-Zadeh (اخلاق وحیانی, 2014)
In the early 1970s, followed by the growth of consumerism in societies, environmental crises such as earth warming and climate change, technological developments and emerging ethical challenges in the global economy, a new movement called "ethical consumerism" was emerged in the field of environmental ethics which aimed to reform different styles of consumption on the based of ethical considerations. By ethical consumerism we mean purchasing the goods and services that implied the least damage to humans, animals and nature in their product and also their consumption. In this context, philosophers, politicians and economic-cultural activists within this movement, tried to offer some appropriate solutions to reduce the damaging effects of human action on the environment. This paper explaining the most important aspects of ethical consumerism and grounds of its formation, criticized the philosophical approaches to this new phenomena, such as deontological approaches, Consequential approaches, and virtue ethics. There is no doubt that in the world that some of the concepts of moral (and immoral) consumption had spread in a large context especially among economists and philosophers, ethical consumption is a controversial and important issue.